Morphological and macroevolutionary analysis of tarsal claws in crab spiders (Thomisidae) - Marques, Jayme Massim (2020)
Claws are important structures in the life of arthropods, helping not only in attachment, but also in food capture, copulation behavior and handling materials for the construction of shelters or traps. In spiders, a polyphyletic group known as Dionycha is characterized by having only two tarsal claws (or a third, extremely reduced) and setae to adhere on smooth surfaces. Within this group is Thomisidae, the seventh largest family of spiders in the world, whose species are ambush hunters who have specialization for capturing prey on their front legs (I and II) and forage, mostly, on aerial parts in plants. Several Thomisidae species show a reduction or absence of these adhesive setae, suggesting that the claw plays the main role in fixing these animals to the substrate. The objective of this study was to compare the morphology of the claws between species in an evolutionary context, to test the existence of sexual dimorphism, to evaluate the morphology of the claws among different legs, to verify the existence of a phylogenetic signal in the morphology of the claws and to test its correlation with the forage substrate of the species. Our results suggest that the morphology of the claws vary only at genus level, with close genera also maintaining several characteristics in common. As expected, due to the high sexual dimorphism in most Thomisidae species, sexual dimorphism was detected in the claws of all analyzed genera. In general, the morphology of the claws corresponds to the pattern described for the legs in the literature for most Thomisidae species: forelimbs (I and II) proportionally larger than the hindlimbs (III and IV). The claws of the forelimbs are larger and less curved than the claws of the hindlimbs. Different from expected, only mesial claws of legs I and II showed a phylogenetic signal greater than that expected at random; an ambiguous result, once most phylogenetically close species and genera did not show significant difference when comparing the claw morphology. Correlation with substrate has been reported for ectal claw of leg I and for mesial claws of legs II, III and IV. However, these results do not seem to correspond to an existing biological pattern, and, considering that species with different claw shapes can forage on the same substrate, we conclude that the claw shape is not correlated with the foraging substrate by itself.